2018
DOI: 10.1128/jvi.00859-18
|View full text |Cite
|
Sign up to set email alerts
|

Sera from Individuals with Narrowly Focused Influenza Virus Antibodies Rapidly Select Viral Escape Mutations In Ovo

Abstract: Influenza viruses use distinct antibody escape mechanisms depending on the overall complexity of the antibody response that is encountered. When grown in the presence of a hemagglutinin (HA) monoclonal antibody, influenza viruses typically acquire a single HA mutation that reduces the binding of that specific monoclonal antibody. In contrast, when confronted with mixtures of HA monoclonal antibodies or polyclonal sera that have antibodies that bind several HA epitopes, influenza viruses acquire mutations that … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 30 publications
2
16
0
Order By: Relevance
“…Our data further show that RBD-12GS-I53–50 elicited Ab responses targeting several of the non-overlapping epitopes recognized by neutralizing Abs that have been identified in the RBD. Such polyclonal responses targeting multiple distinct epitopes might explain the magnitude of neutralization observed and should minimize the risk of selection or emergence of escape mutations ( Davis et al, 2018 ; Lee et al, 2019 ). Finally, the high production yield of RBD-I53–50A components and the robust stability of the antigen-bearing RBD nanoparticles suggests that these will likely be more amenable to large-scale manufacturing than the SARS-CoV-2 S-2P trimer, which expresses poorly and is unstable ( Edwards et al, 2020 ; Hsieh et al, 2020 ; McCallum et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Our data further show that RBD-12GS-I53–50 elicited Ab responses targeting several of the non-overlapping epitopes recognized by neutralizing Abs that have been identified in the RBD. Such polyclonal responses targeting multiple distinct epitopes might explain the magnitude of neutralization observed and should minimize the risk of selection or emergence of escape mutations ( Davis et al, 2018 ; Lee et al, 2019 ). Finally, the high production yield of RBD-I53–50A components and the robust stability of the antigen-bearing RBD nanoparticles suggests that these will likely be more amenable to large-scale manufacturing than the SARS-CoV-2 S-2P trimer, which expresses poorly and is unstable ( Edwards et al, 2020 ; Hsieh et al, 2020 ; McCallum et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Foundational work on the theory of original antigenic sin demonstrated that an individual’s immune response to influenza vaccination is biased toward antigens similar to those encountered in childhood ( Davenport and Hennessy, 1956 ). In some cases, this may result in a narrow antibody response focused on a single epitope ( Davis et al, 2018 ). This phenomenon has been suggested to explain an unexpected decrease in vaccine effectiveness (VE) in the middle-aged in the 2015–2016 influenza season ( Skowronski et al, 2017b ; Flannery et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…The observation that immune escape can be reliably be selected for in egg (Davis et al, 2018) and mouse (Hensley et al, 2009) passage experiments and yet appears rare in reinfected experienced humans is unsurprising in light of our view that influenza virus evolution is limited more by the failure of selection pressure and antigenic diversity to coincide than by the absence of either.…”
Section: Discussionmentioning
confidence: 99%